AI Marketing Impact on Consumer Behavior: An SOR Model Analysis of Online Food Delivery Services - Vindytia, Mona; Balqiah, Tengku Ezni (Universitas Negeri Semarang, 2024)
Today’s world thrives on artificial intelligence’s (AI) ability to unlock new and exciting ways to engage customers. By powering innovative offerings and personalized experiences, AI strengthens the bond between brands and their consumers, setting them apart from the competition. According to the Stimulus–Organism–Response (SOR) model, this study aims to analyze how stimulus factors in Artificial Intelligence (AI) marketing efforts impact consumer behavior in food delivery service applications. This research uses a quantitative, descriptive, and cross-sectional survey approach. Structural Equation Model (SEM) was used to analyze 412 responses from a questionnaire survey of Generation Y and Z subjects who used food delivery service applications from 2 leading platforms in the industry, such as Gojek (GoFood) and Grab (GrabFood). The results showed that all stimulus factors in AI marketing efforts affect brand experience, while only information and interaction affect brand equity. Both brand experience and equity significantly influence responses (brand preference and reuse intention). Implications of this study can activate academia and business practitioners to understand the influence of AI on user experiences and provide a guide for the development of marketing and branding strategies to strive for customer satisfaction by offering online service.